2001
DOI: 10.1046/j.1365-2982.2001.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal pressure–cross‐sectional area distributions and secondary peristalsis in relation to subclassification of systemic sclerosis

Abstract: The aim of the present study was to correlate the severity of oesophageal motor dysfunction with the severity of cutaneous disease in systemic sclerosis (SS). Patients were divided into three groups based on the degree of skin involvement: type I, acrosclerosis distal to the wrist; type II, scleroderma extending above the wrist in proximal direction; type III, diffuse cutaneous systemic sclerosis. Impedance planimetry employing distensions with pressures up to 5 kPa with the concomitant measurement of oesophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 27 publications
1
41
1
3
Order By: Relevance
“…The interested reader is referred to those and other publications for methodological and analytical considerations and interpretation of the in vivo muscle function curves [10,13,15,[18][19][20][21][22][23][24][25]. Corresponding analysis on length-tension relations in muscle strips in vitro has been described in other papers [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The interested reader is referred to those and other publications for methodological and analytical considerations and interpretation of the in vivo muscle function curves [10,13,15,[18][19][20][21][22][23][24][25]. Corresponding analysis on length-tension relations in muscle strips in vitro has been described in other papers [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The patients and volunteers in this study, including demographic and clinical data, have been described in detail by Villadsen and coworkers [9]. In brief, eleven patients (8 women and 3 men, average age 51.2 ± 9.2 (range 33-71) years) suffering from SS and abnormal esophageal motility were included in the study.…”
Section: Subjectsmentioning
confidence: 99%
“…Thus, measurements are obtained at one specific locus. Furthermore, CSA is more closely associated with the diametrical changes in the esophageal lumen than volume is [9][10][11]. Previous mechanical studies of SS patients using impedance planimetry have shown esophageal and duodenal dilatation, wall stiffening, and reduced muscle contractility [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Esophagus is the most commonly affected organ, occurring in up to 90% of patients with SSc. [1][2][3] Clinically it is characterized by symptoms of gastroesophageal reflux disease (GERD) and of esophageal motor dysfunction. Typical symptoms of heartburn and dysphagia are reported by 80% of patients.…”
Section: Introductionmentioning
confidence: 99%